Occupational choice, aggregate productivity, and trade - Jürgen Meckl; Benjamin Weigert (Institute for the Study of Labor (IZA), 2011)
We propose occupational decisions of heterogeneous individuals as an alternative mechanism of explaining the distribution of firm productivities emphasized by empirical studies. Thus, we integrate the frameworks of Melitz (2003), and of Manasse and Turrini (2001) that establish the theoretical base of trade models with heterogeneous firms. Our model is technically much simpler than the Melitz approach while preserving the main results on firm-selection effects due to international market integration. Our approach paves the way for detailed analysis of institutions in a heterogeneous firm model to better understand the link between institutions and an economy's productivity distribution.
urn:nbn:de:101:1-201104113700
Keywords: F12; F16; J24; 330; intra-industry trade; heterogeneous productivities; firm selection; occupational choice; Produktivität; Branchenentwicklung; Strukturwandel; Berufswahl; Allokation; Intraindustrieller Handel; Außenhandelsliberalisierung; Theorie